Dental students’ perception towards online MCQ tests - Rajeshwar Reddy Kasarla; Kripa Ghimire; Nikita Singh Yadav (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: College of Dental Surgery, Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal conducted online assessment MCQ tests during covid-19 lock down period. This study was taken up to measure/assess the BDS students’ perception towards online assessment MCQ tests conducted during the COVID-19 lockdown period. Materials and Methods: A descriptive, cross-sectional study was conducted by administering Google Forms questionnaire to BDS students of College of Dental Surgery, UCMS during the period the period of 2 October 2021 to 30 December 2021, using non-probability purposive sampling. General information proforma for socio-demography, and a questionnaire on the lines of Likert’s summated rating scale to assess the perception of BDS students towards online assessment was constructed. Simple frequency tables, cross tables, and mean tables have been used to analyze data. Characteristics of the sample were categorized using mean and standard deviation. Results: The overall mean and standard deviation for perception of online assessment tests were 3.31 and 0.77 respectively. The results indicate that BDS students were satisfied with online assessment tests. Conclusion: Online assessment tests were well received by BDS students. The online assessment tests enhance student learning by allowing immediate feedback. Online tests should be conducted in dental colleges on a regular basis.